JÚREK-QAN TAMÍR SISTEMASÍNA TABIYIY KLIMAT JAǴDAYLARÍNÍŃ TÁSIRI - Begdullaeva, G.; Maulenova, D.; Seytkamalov, X. (SCIENCE and SOCIETY, 2025)
The article analyzes modern data reflecting the impact of natural climatic factors on the human cardiovascular system through literature review. According to the literature, the most important natural and climatic factors are environmental parameters such as temperature, atmospheric pressure, and solar activity. It has been established that the above-mentioned factors have a strong influence on the cardiovascular system, which can be observed in the development of such specific cases as stroke, myocardial infarction, and sudden coronary death.